Fry growth modelling in Cichlasoma festae (Cichlidae) with Biobloc technology (BFT) (Veterinary Science, 2020)
Aquaculture favors food sovereignty in Equator, maintains their livelihoods and boosts household unit incomes. The freshwater species Cichlasoma festae represents an important species of great local use. In this study, our objective was to model fry growth in Cichlasomafestae, produced in intensive systems with Biobloc technology. The study lasted 90 days and was carried out in the experimental farm “La María”, in Quevedo Local Technical University (UTEQ). 15 cages were placed inside a reinforced concrete circular pond with Biobloc and 300fries from C. festae with a weight of 4,9g were introduced. Individual biometric parameters of total length, weight and height were fortnightly measured in 75 fries from C. festae. Physicochemical parameters of Biobloc water (PH, temperature, oxygen, total ammoniacal nitrogen and suspended solids) were daily measured. Growth was determined using regression models and in a second stage the weight was adjusted to the best fit selected model, which was: Log-Y Square root-X which explains the 98,3% of the variability in weight. We may conclude with this study that Biobloc technology could be an alternative for intensive native species production. In future research, it will be necessary to advance in the knowledge of Biobloc conditions for each species, production biomass, aeration strategies for each growth stages and thus boost and optimize farming.
Keywords: Conservation; Native species; Technological innovation; Growth models